Graphene-induced hierarchical mesoporous MgO for the Claisen–Schmidt condensation reaction. (21st February 2019) - Qi, Xiaoxia; Yan, Xirui; Peng, Wencai; Zhang, Jianshu; Tong, Yanbin; Li, Jun; Sun, Dekui; Hui, Ge; Zhang, Jinli
Abstract : Multistage mesoporous magnesium oxide prepared by a simple hydrothermal method has an ideal particle size, channel distribution, active crystal face, good catalytic activity and regeneration ability. Abstract : Hierarchical mesoporous MgO (HMM) is synthesized in the presence of graphene by a simple hydrothermal homogeneous precipitation route using urea as the precipitating reagent. Characterization of the HMM particles by means of spectroscopy and microscopy techniques, among others, indicates that HMM exposes the (111) crystal faces and possesses a specific surface area of 138 m 2 g −1 and a pore size of about 0.33 m 2 g −1 . HMM exhibits higher activity for the Claisen–Schmidt condensation reaction than a conventionally prepared MgO catalyst, with a maximum turn over frequency of 1.34 × 10 −4 s −1 . Since the deactivation of the catalyst is mainly due to the formation of polyaromatic ketones in the reaction process, the catalyst can be readily regenerated through calcination.